The Effect of Modified Tape’s starter on Characteristics of Tape Injin (Oryza sativa glutinosa) - Oktaviana Dewi, Desak Made; Kencana Putra, I.N.; Suparthana, I.P. (Journal of Food Security and Agriculture; Vol 1 No 2 (2017): Journal of Food Security and Agriculture, 2017)
Tape injin is a Balinese traditional fermented product made from black sticky rice (injin). It’s production by using common starter which's usually sold in public market resulting in unstable quality and even fail of tape injin. This study aimed to determine the effect of modified tape’s starter utilization on characteristic of tape injin. The experiment was designed as a randomized block design by using five treatments which were the utilization of 0.6%, 0.9%, 1.2%, 1.5% of modified tape’s starter including 0.3% of control. The treatment was repeated 3 times. The parameters observed namely pH, total molds and yeasts, total alcohol, total acid and sensory evaluation (taste, color, aroma, texture and overall acceptance). Data were analyzed by variance, and if found any effect on the treatment, the analysis continued by Duncan's test. The results showed that the utilization of modified tape’s starter significantly affect the pH, total alcohol, total acid, flavor, color, aroma, texture and overall acceptance. The utilization of 1.5% modified tape’s starter produces the best characteristics of tape injin with pH 4.04, total alcohol: 2.77%; total acid: 1.12%, and 6.3 value (be liked) of overall acceptance by sensory evaluation.